Multi-omics analysis reveals that low cathepsin S expression aggravates sepsis progression and worse prognosis via inducing monocyte polarization - Luo, Xiao-Ting; Hu, Hui-Rong; Sun, Zhen-Dong; Zhang, Li-Hong; Li, Yan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundMonocytes represent a vital cellular subpopulation in the peripheral blood, crucial in the progression of sepsis. Nonetheless, the prognostic role and precise function of monocytes in sepsis are still inadequately understood.MethodsSingle-cell transcriptomic sequencing and bioinformatics analysis were performed on peripheral blood samples from septic patients to identify key molecules in cell subsets. Subsequently, the expression pattern of this molecule was validated through diverse biological experiments, encompassing quantitative RT-PCR, western blotting, and immunofluorescence. Finally, the functionality of this molecule was evaluated using its specific agonist.ResultsA total of 22 monocytes-related biomarkers were identified from single-cell and bulk RNA-seq analyses. Initially, LASSO analysis was performed to derive a prognostic signature composed of 4 key genes, including CD14, CTSS, CXCL8 and THBS1. Subsequently, mendelian randomization and survival analysis demonstrated that only CTSS showed crucially protective role in sepsis development and prognosis. Next, CTSS was confirmed to be lower expressed in peripheral monocytes of septic patients. Inflammatory markers (p < 0.05) and migration ability of LPS-activated monocytes were significantly reduced after CTSS agonist. In addition, CTSS agonist decreased the pulmonary tissue monocyte/macrophages infiltration in septic mice.ConclusionMonocyte marker CTSS represent a promising target for the diagnosis and prognosis evaluation of sepsis and plays a critical role in monocytes activation, tissue inflammatory response and macrophages infiltration. Thus, CTSS agonist probably serves as new drug for clinical protection against sepsis.